A broader mission for R&D - Miller, William L.
William L. Miller outlines a new innovation system, called Fourth Generation R&D, designed to eradicate the isolated groups of practice that characterize the traditional innovation system.
In a new innovation system, fusing R&D with expeditionary marketing creates a shared learning environment in which customers and suppliers experience future capabilities together.
Improving the effectiveness of innovation requires R&D management to resolve the dilemma of risk management through the discovery of competitive capabilities for unclear stakeholder requirements. Mutually dependent learning must occur across separate groups : R&D, suppliers, customers, marketing, and other stakeholders. They must learn which new capabilities can be economically developed and how latent demands among potential customers can be met by those new capabilities. Because customers and other stakeholders need to experience new capabilities to adequately understand and assess their value, traditional market research is inadequate in revealing latent needs. To help resolve the dilemma, R&D is redefined in a new innovation system with a focus on leveraged and concurrent shared learning. Participatory research with stakeholder testing of prototypes is coupled with a new business process that concurrently develops capabilities and architecture. Architecture includes product platforms. The new innovation system, called Fourth Generation R&D, can improve the effectiveness of both incremental and radical R&D. The broader mission for R&D and the new innovation system complements recent concepts of business strategy such as strategic intent, core competencies, strategic architecture and expeditionary marketing.